LITERATUR RIVIEW: PERUBAHAN MATERI GENETIK - Kinanti, Aulian Andin; Khairani , Miftahul; Syahfitri , Dini Indah; Lubis , Fazil Mawla; Sinurat , Yulianti (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Human creation must be understood through stages of growth and development, where in the process of growth and development humans experience interactions or relationships that influence each other between basic abilities or innate abilities and acquired abilities, namely through learning and influence from the environment. This research was conducted by analyzing 10 journals. The keywords used were